Driver Influence on Vehicle Track-Ability on Floating Bridges - Gustafsson, Adam; Svensson, Christian; Berg, Ivan; Johnsson, Jonas; Lubell, Moa (My University, 2019)
The Norwegian highway route E39 consists of many different ferry connections, which results in a travel time of 21 hours for a travel distance of 1100 km from Kristiansand to Trondheim. The Norwegian government has therefore decided to invest in new infrastructure, which would reduce the travel time to about half. One of these solutions are to implement floating bridges. Floating bridges have the capacity to cross large distances such as fjords, but would also introduce motion to the vehicles driving upon it. Having waves and wind affecting the bridge, and crosswind directly affecting the vehicle, makes it difficult to assess the problem using existing theoretical methods. Therefore, a method to investigate how a moving road surface will affect the vehicle and the driver needs to be developed in this project. The study utilized a industry-grade motion driver-in-the-loop simulator. This report describes how the method for testing these driving conditions was achieved and assesses the validity of using such method. The conclusion was that the method of evaluating the driver influence on track-ability on floating bridges is functional.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering